Identification of Amino Acid Residues in Human IgM Fc Receptor (FcµR) Critical for IgM Binding - Skopnik, Christopher M.; Al-Qaisi, Khlowd; Calvert, Rosaleen A.; Enghard, Philipp; Radbruch, Andreas; Sutton, Brian J.; Kubagawa, Hiromi (Frontiers in Immunology, 2021)
Both non-immune “natural” and antigen-induced “immune” IgM are important for protection against infections and for regulation of immune responses to self-antigens. The roles of its Fc receptor (FcµR) in these IgM effector functions have begun to be explored. In the present study, by taking advantage of the difference in IgM-ligand binding of FcµRs of human (constitutive binding) and mouse (transient binding), we replaced non-conserved amino acid residues of human FcµR with mouse equivalents before establishment of cell lines stably expressing mutant or wild-type (WT) receptors. The resultant eight-different mutant FcµR-bearing cells were compared with WT receptor-bearing cells for cell-surface expression and IgM-binding by flow cytometric assessments using receptor-specific mAbs and IgM paraproteins as ligands. Three sites Asn66, Lys79-Arg83, and Asn109, which are likely in the CDR2, DE loop and CDR3 of the human FcµR Ig-like domain, respectively, were responsible for constitutive IgM binding. Intriguingly, substitution of Glu41 and Met42 in the presumed CDR1 with the corresponding mouse residues Gln and Leu, either single or more prominently in combination, enhanced both the receptor expression and IgM binding. A four-aa stretch of Lys24-Gly27 in the predicted A ß-strand of human FcµR appeared to be essential for maintenance of its proper receptor conformation on plasma membranes because of reduction of both receptor expression and IgM-binding potential when these were mutated. Results from a computational structural modeling analysis were consistent with these mutational data and identified a possible mode of binding of FcµR with IgM involving the loops including Asn66, Arg83 and Asn109 of FcµR interacting principally with the Cµ4 domain including Gln510 and to a lesser extent Cµ3 domain including Glu398, of human IgM. To our knowledge, this is the first experimental report describing the identification of amino acid residues of human FcµR critical for binding to IgM Fc.